Development of Digital Technologies in Public Administration in Socio-Economic Areas - Karimov, T. X. (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Goals and objectives of the "Uzbekistan-2030 Digital" strategy, normative legal documents related to the digital transformation of industries in the Republic of Uzbekistan, the strategic goals and priorities of digital development, the projects implemented within the framework of the "Uzbekistan 2030 Digital" strategy are described.